Effect of pelvic position on ultrasonic measurement parameters of pelvic floor in postpartum women - Yu Wang; Yan Zhuo; Min Liu; Jianqi Fang; Zongjie Weng (BMC Women's Health)
Abstract Objective To analyse the effect of pelvic position on ultrasonic measurement parameters of pelvic floor in postpartum women. Methods This study included 132 postpartum participants who visited Fujian Maternity and Child Health Hospital from May 2020 to May 2024. All participants were assessed by medical professionals for general information and pelvic floor four dimensional ultrasound. Ultrasonic measurements were performed in three different positions of the pelvis (anterior pelvic tilt, posterior pelvic tilt, and neutral pelvic tilt) based on lithotomy position. Results Our results indicated that the differences in the diagnosis of cystocele, uterine prolapse, perineal overactivity, and hiatal ballooning among the neutral position, anterior pelvic tilt, and posterior pelvic tilt were statistically significant (P<.001, P<.001, P<.001, and P<.001 respectively). The differences among neutral pelvic tilt, anterior pelvic tilt, and posterior pelvic tilt in hiatal area (during contraction), hiatal area (during rest), hiatal area (during valsalva), bladder neck descent, urethral rotation angle, cervical descent, rectal ampulla descent, hiatal area increase, and hiatal area decrease were statistically significant (P <.001, P <.001, P <.001, P <.001, P <.001, P <.001, P <.001, P <.001, and P <.001 respectively), with almost all the values of those parameters in posterior pelvic tilt the highest among three groups. The differences in cervical position (at rest), rectal ampulla position (at rest), and bladder neck position (during valsalva), cervical position (during valsalva), and rectal ampulla position (during valsalva) among neutral pelvic tilt, anterior pelvic tilt, and posterior pelvic tilt were statistically significant (P <.001, P =.035, P <.001, P <.001, and P <.001 respectively), with almost all the values of those parameters in posterior pelvic tilt the lowest among three groups. Conclusion During the pelvic floor muscle contraction, the posterior pelvic tilt showed the most reduction of hiatal area compared to that in other positions. During Valsalva, not only the most increase of the hiatal area, but also the greatest bladder neck descent, cervical neck descent, and rectal ampulla descent were observed in the posterior pelvic tilt position.